GERMINATION AND VIGOR OF LETTUCE SEEDS UNDER DIFFERENT TEMPERATURES - Maia Soares, Patricia Aparecida; Santos de Souza David, Andreia Márcia; Mota Pinheiro Bernardino, Dayana Lucia; de Azevedo Quintino, Renato; Nunes Lacerda, João Paulo; Gomes da Silva, Fernando (REVISTA DE AGRICULTURA, 2017)
The objective of this study was to evaluate the effect of temperature on germination and vigor of the seeds of different lettuce cultivars. It was used a completely randomized design in a factorial arrangement 4x3, with four cultivars (American, Crespa para Verão, Mimosa Salad Bowl, and Crespa Repolhuda) and four temperatures (20, 25, 30 and 35°C), with four replicates per treatment. The effects of the treatments were evaluated by germination and vigor tests (first count, germination speed index). There was influence of the lettuce grow crops on germination and seed vigor. The cultivars of the lettuce have a higher germination and vigor when exposed to 20°C, and the Crespa for daylight showed itself more tolerant to temperatures of 25 to 30°C. The temperature of 30°C inhibits the germination of lettuce seeds of the Americana, Mimosa Salad bowl and Crespa Repolhuda cultivars